Imperial Urbanism in the Borderlands : Kyiv, 1800-1905 - Bilenʹkyĭ, Serhiĭ (Book collections on Project MUSE., 2018)
"In the nineteenth and early twentieth century Kyiv was an important city in the European part of the Russian empire, rivaling Warsaw in economic and strategic significance. It also held the unrivaled spiritual and ideological position as Russia's own Jerusalem. In Imperial Urbanism in the Borderlands, Serhiy Bilenky examines issues of space, urban planning, socio-spatial form, and the perceptions of change in imperial Kyiv. Combining cultural and social history with that of urban studies, Bilenky unearths a wide range of unpublished archival materials and argues that the changes experienced by the city prior to the revolution of 1917 were no less dramatic and traumatic than those of the Communist and post-Communist era. In fact, much of Kyiv's contemporary urban form, architecture, and natural setting were shaped by imperial modernizers during the long nineteenth century. The author also explores a general culture of imperial urbanism in Eastern Europe. Imperial Urbanism in the Borderlands is the first work to approach the history of Kyiv from an interdisciplinary perspective and showcases Kyiv's rightful place as a city worthy of attention from historians, urbanists, and literary scholars."--